Evidence-Informed Facilitated Feedback: The R2C2 Feedback Model - Joan Sargeant; Heather Armson; Erik Driessen; Eric Holmboe; Karen Könings; Jocelyn Lockyer; Lorna Lynn; Karen Mann; Kathryn Ross; Ivan Silver; Sophie Soklaridis; Andrew Warren; et al. (Association of American Medical Colleges, 2016)
Abstract Introduction While feedback continues to pose challenges, new understanding is emerging. Feedback is now being seen as an interaction in which learner engagement, supportive relationships, reflection, and cooperative planning are important. In response and through research, we developed and tested the R2C2 model and teaching materials to support its use. Methods R2C2 is an evidence-based reflective model for providing assessment feedback. It includes four phases: (1) relationship building, (2) exploring reactions to the feedback, (3) exploring understanding of feedback content, and (4) coaching for performance change. It provides a strategy for facilitating feedback conversations that promote engagement with performance data and enable coaching for improvement. This package of educational materials includes paper-based and video resources designed to support interactive learning and skills development in facilitating feedback and coaching. Specific strategies are described and demonstrated for each phase of the R2C2 model and include a learning change template for the coaching phase. Resources can be used by an individual or group. A workshop outline with presentation slides and a practice scenario are also included. Results Through research, invited and peer-reviewed presentations, and feedback from colleagues who have used the materials and the R2C2 model, we have learned that the model is intuitive and easy to use, that it can engage the learner and support coaching, and that the educational materials are clear and useful. Discussion The model is intuitive, especially within competency-based education, is easy to follow, and makes sense to faculty, which makes it easy to implement in most programs.